Menjembatani kurikulum resmi dan kurikulum yang ditujukan guru melalui penelitian tindakan - Sekar Syawalahayati; Zainal Arifin (Curricula: Journal of Curriculum Development, 2026)
A persistent challenge in curriculum implementation is the gap between educational policies and classroom teaching practices, particularly in how teachers translate the official curriculum into contextualized instructional plans at the teacher-intended stage. This study aims to analyze how action research can strengthen teachers’ roles in bridging this translation process. This study employs a literature review using a descriptive-analytical approach, drawing on scholarly sources from academic databases related to curriculum, teacher professionalism, and action research. The findings indicate that through cycles of planning, action, and reflection, action research supports teachers in identifying learning problems, making data-informed instructional decisions, and adapting teaching strategies to students’ needs. In this way, the translation of the curriculum becomes more contextual and responsive to classroom realities. However, its effectiveness depends on institutional support, collaboration, and opportunities for continuous professional learning. Therefore, action research helps address the gap between policy and practice while supporting teachers’ professional capacity in curriculum decision-making.